2021
DOI: 10.1111/wre.12470
|View full text |Cite
|
Sign up to set email alerts
|

Windows of action for controlling palmer amaranth (Amaranthus palmeri) using emergence and phenology models

Abstract: Amaranthus palmeri S. Watson has become a weed of economic importance throughout the South-eastern United States in the last 20 years (Webster and Nichols, 2012) being especially problematic in soyabean (Glycine max L. Merr.) and cotton (Gossypium hirsutum L.) fields (Bensch et al., 2003;Berger et al., 2015). Recently, multiple reports have indicated that this weed species is invading agricultural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Redroot pigweed demonstrated a range of emergence peaks from spring to summer (Table 1, Figure 2). This protracted emergence pattern of Amaranthus species has been well-described in the literature (Jha and Norsworthy, 2009;Teasdale and Mirsky, 2015;Chahal et al, 2021;Reinhardt Piskackova et al, 2021).…”
Section: Results By Speciessupporting
confidence: 72%
See 2 more Smart Citations
“…Redroot pigweed demonstrated a range of emergence peaks from spring to summer (Table 1, Figure 2). This protracted emergence pattern of Amaranthus species has been well-described in the literature (Jha and Norsworthy, 2009;Teasdale and Mirsky, 2015;Chahal et al, 2021;Reinhardt Piskackova et al, 2021).…”
Section: Results By Speciessupporting
confidence: 72%
“…Early planting of spring-planted crops may be used to establish a size advantage over mid-season weeds that can be used to improve control (Mohler, 2001). This size advantage is especially important for keeping weeds as small as possible for late post-emergence herbicide applications (Reinhardt Piskackova et al, 2021) and improving the selectivity of intrarow cultivation (Gallandt et al, 2017). The effect of early planting can perhaps be strengthened by additional weed suppressive tactics.…”
Section: Weeds With Mid-season Peak Emergencementioning
confidence: 99%
See 1 more Smart Citation
“…Narrow‐windrow burning is another non‐chemical strategy that seems quite promising to destruct Amaranthus palmeri seeds 75 and not allow seeds to enter the soil seedbank. Emergence and phenology models are useful tools to assist the decision‐making process for the management of Amaranthus palmeri and identify the critical time for treatment 76 . It is crucial to prevent the introduction of Amaranthus palmeri seeds that could invade and possess new herbicide resistance traits, making the management even more challenging 54 .…”
Section: Integrated Management Of Important Ips: Two Case‐studiesmentioning
confidence: 99%
“…It has been reported that the flowering of A. palmeri occurs during Spring to Summer with subsequent seed development and seed set occurring in as little as two to three weeks post‐fertilisation (Keeley et al, 1987; Sosnoskie et al, 2012). Research suggests that A. palmeri emergence primarily occurs during Summer, although it is suggested that over 90% of total season growth may occur earlier in the season or in late Spring to early Summer in the absence of competition (Reinhardt Piskackova et al, 2021). The germination of A. palmeri occurs across a two‐month period between Spring and early Summer, where seeds will germinate when soil temperatures are on average greater than 25 O C but less than 35 O C (Guo and Al‐Khatib, 2003; Jha and Norsworthy, 2009).…”
Section: Biology and Ecologymentioning
confidence: 99%